EFFECT OF PARTIAL REPLACEMENT OF CEMENT WITH GROUND GRANULATED BLAST FURNACE SLAG IN CONCRETE - Salahuddin Shakeeb S M (International Educational Journal of Science and Engineering, 2026)
The present paper examines the effect of using Ggbs as partial replacement of cement in producing a engineered cementitious composites. In recent years Ggbs when replaced partial with cement has emerged as a major alternative to conventional concrete and has rapidly drawn the concrete industry attention during to its energy savings, cement savings, cost savings, environmental and socio-economic benefits. Effect of replacement was seen on compressive strength, tensile strength and modulus of rupture by casting mixes of grades M20, M30 and M40 and cement replacement adopted was 0 %, 15%, 30%, 40%, 50%. Here an effort is made towards a specific understanding of the efficiency of Ggbs in the concrete, strength develop, low heat of hydration, resistance to chemical attack, better workability, good durability and cost effective.